Step
*
1
2
1
1
2
1
of Lemma
converges-to-rexp
1. m : ℤ
2. 0 < m
3. e^r(m - 1) ≤ r(3^m - 1)
4. e^r(m) = (e^r(m - 1) * e^r1)
⊢ (e^r(m - 1) * e^r1) ≤ r(3^m)
BY
{ (RWO "-2" 0 THENA Auto) }
1
.....rw func antecedent..... 
1. m : ℤ
2. 0 < m
3. e^r(m - 1) ≤ r(3^m - 1)
4. e^r(m) = (e^r(m - 1) * e^r1)
⊢ ((r0 ≤ e^r(m - 1)) ∧ (r0 ≤ e^r1)) ∨ ((r0 ≤ e^r1) ∧ (r0 ≤ r(3^m - 1)))
2
1. m : ℤ
2. 0 < m
3. e^r(m - 1) ≤ r(3^m - 1)
4. e^r(m) = (e^r(m - 1) * e^r1)
⊢ (r(3^m - 1) * e^r1) ≤ r(3^m)
Latex:
Latex:
1.  m  :  \mBbbZ{}
2.  0  <  m
3.  e\^{}r(m  -  1)  \mleq{}  r(3\^{}m  -  1)
4.  e\^{}r(m)  =  (e\^{}r(m  -  1)  *  e\^{}r1)
\mvdash{}  (e\^{}r(m  -  1)  *  e\^{}r1)  \mleq{}  r(3\^{}m)
By
Latex:
(RWO  "-2"  0  THENA  Auto)
Home
Index